Proceedings of the 2nd International Conference on Intervention and Applied Psychology (ICIAP 2018) 2019
DOI: 10.2991/iciap-18.2019.78
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Leadership and Work Engagement: The Role of Psychological Empowerment as a Mediator

Abstract: Millennials' domination of the workplace has resulted in increasing attention to the issue of engagement. Leaders need to enhance their understanding of leadership empowerment behavior as a means to increase employee engagement. Psychological empowerment encompasses a set of conditions necessary for intrinsic motivation and has been proposed as a mediator in the relationship between empowerment leadership and work engagement. This study explores the mediating role of psychological empowerment in relations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
2
5
0
2
Order By: Relevance
“…This finding is in line with the results of research by Alotaibi et al (2020), who found employees who felt empowered by their superiors would be motivated to be more engaged with their work and company. The same finding was found in the research of Qatrunnada and Parahyanti (2019). Empowering leaders' behavior, such as: working harder than a team member, coaching teams to be self-reliant, encouraging highperforming teams by showing confidence in their competence providing opportunities to participate in decision making, sharing new information, showing concern, and interacting with teams can increase employee psychological empowerment, which in turn increases their employee engagement.…”
Section: B Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is in line with the results of research by Alotaibi et al (2020), who found employees who felt empowered by their superiors would be motivated to be more engaged with their work and company. The same finding was found in the research of Qatrunnada and Parahyanti (2019). Empowering leaders' behavior, such as: working harder than a team member, coaching teams to be self-reliant, encouraging highperforming teams by showing confidence in their competence providing opportunities to participate in decision making, sharing new information, showing concern, and interacting with teams can increase employee psychological empowerment, which in turn increases their employee engagement.…”
Section: B Discussionsupporting
confidence: 80%
“…Furthermore, found empowering leader behaviors, such as: working harder than team members, coaching teams to be more self-reliant, encouraging high-performing teams by showing confidence in their competence, providing opportunities to participate in decision making, sharing new information, showing concern, and interacting with the 1.386 http://eduvest.greenvest.co.id team will increase psychological empowerment which in turn increases employee engagement. Some consultants and researchers explained that employee development factors also affect employee engagement (Qatrunnada & Parahyanti, 2019) defined employee development as an effort to increase an employee's technical, theoretical, conceptual, and moral abilities that are relevant to the needs of the job or position through education and training. Employees feel more engaged when the company provides opportunities and support for employee development through job rotation, on-the-job learning, or training programs to improve their current job skills.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the empowerment of leader behavior, the more employees feel psychologically empowered, which in turn makes employees feel more involved in work (34). Empowered employees report high job satisfaction for individuals (35,36) and teams (37).…”
Section: Impact Of Empowering Leadership On Work Engagementmentioning
confidence: 99%
“…It has been manifested as one of the outcomes of adopting empowering leadership style (Alotaibi, Amin, & Winterton, 2020;Kundu et al, 2019). Moreover, it's recognized as a mediator between empowering leadership and work engagement (Qatrunnada & Parahyanti, 2019). Although many researches have underscored its importance as a critical mediator but very few researches have probed its moderating effect.…”
Section: Moderating Role Of Psychological Empowermentmentioning
confidence: 99%